A mild phenotype associated with a de novo microdeletion 10q23.1-q23.2: a new patient with a novel feature. (18th April 2016) - Pavone, Piero; Praticò, Andrea D; Campisi, Corrado; Falsaperla, Raffaele
Abstract : Chromosome 10q23 contains several genes, including PTEN and BMPR1A, the mutations or microdeletion of which are associated with aggressive polyposis and malignancies in children. Deletions in this chromosomal region have also been associated with heart anomalies, developmental delay and macrocephaly. Most of the cases reported involve the PTEN and BMPR1A genes, usually associated with complex and severe anomalies. We report a case of a boy with a de novo interstitial microdeletion in 10q23.1-q23.2 spanning 6.7 Mb with boundaries from 82 087 077 to 88 847 906, not including PTEN and BMPR1A . Clinical features consisted of mildly dysmorphic facies, frontal telangiectasias, poor scholastic performance and hyperactivity. Furthermore, the boy presented toe anomalies, which appeared to be novel features associated with 10q23 deletion. Further observations of 10q23.1-q23.2 deletions are necessary to confirm the clinical features observed in the proband, and to show that deletion or mutations not involving PTEN and BMPR1A may not be associated with severe neurological impairment and malformation anomalies.